2013
DOI: 10.1590/s2317-15372013000400001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Sclerotinia sclerotiorum and the physical and physiological quality of soybean seeds based on processing stages

Abstract: Soybean (Glycine max L. Merrill) is infected by a large number of fungal pathogens, among them white mold agent [Sclerotinia sclerotiorum (Lib) de Bary]. The objective of this study was to verify the effect of the seed-processing stages on the physical and physiological qualities and on the incidence of S. sclerotiorum in soybean seeds. In this study, seeds from eight cultivars coming from production fields naturally infested in the counties of the State of Goiás, Brazil, from two harvests (2009/2010 and 2010/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…In studies carried out in the field by Garcia, Juliatti (2012) and Juliatti et al (2013), the genotype Emgopa 316 was also considered resistant to the disease when compared to other genotypes. In a study conducted in the crop season 2010/ 2011 using cultivar NA 7255 RR, Teles et al (2013) observed a higher incidence of sclerotia in seed samples. The same author reported that the amount of sclerotia in the sample was not necessarily correlated with the incidence of S. sclerotiorum in the mycelial form in soybean seeds.…”
Section: Resultsmentioning
confidence: 92%
“…In studies carried out in the field by Garcia, Juliatti (2012) and Juliatti et al (2013), the genotype Emgopa 316 was also considered resistant to the disease when compared to other genotypes. In a study conducted in the crop season 2010/ 2011 using cultivar NA 7255 RR, Teles et al (2013) observed a higher incidence of sclerotia in seed samples. The same author reported that the amount of sclerotia in the sample was not necessarily correlated with the incidence of S. sclerotiorum in the mycelial form in soybean seeds.…”
Section: Resultsmentioning
confidence: 92%
“…O bom desempenho de uma cultura depende da qualidade das suas sementes, pois elas contêm todo o potencial genético que a planta pode expressar (MENEZES et al, 2011 No Brasil, tem-se verificado a preocupação com relação à infecção das sementes por micélio de S. sclerotiorum (HENNEBERG et al, 2012;BOTELHO et al, 2013;TELES et al, 2013), todavia, a taxa de transmissão do patógeno, para muitos de seus hospedeiros, ainda não foi quantificada, tampouco, tem-se relacionado a infecção fúngica com o vigor de sementes e desenvolvimento de plantas. Diante do contexto, o trabalho propôs-se a verificar a transmissibilidade de S. sclerotiorum a partir de sementes de canola, cártamo, crambe, girassol, nabo forrageiro e níger, inoculadas artificialmente, às suas plântulas, assim como avaliar a sua relação e implicação sobre a emergência de plântulas.…”
Section: Introductionunclassified